10.1016/S0271-7964(08)70570-6 (CrossRef Listing of Deleted DOIs, 2000)
Purpose 4D cardiac cine is a powerful tool for comprehensive cardiac function assessment; however, current methods rely on regular breathing and are sensitive to bulk motion and arrhythmia. We aim to develop a 4D cardiac cine approach that requires no patient cooperation and is robust to irregular breathing, bulk motion, and cardiac arrhythmia. Methods 2D real-time (RT) spiral bSSFP with synchronized ECG was acquired in 4 cardiac orientations. In each orientation, the 2D slice was "swept" across the heart to provide volume coverage. Retrospectively gated slice-to-volume reconstruction (SVR) was then performed to reconstruct 4D cine with 1 mm 3 voxel size and 25 cardiac phases. RT-SVR and clinical standard breath-hold short-axis cine were acquired in 19 subjects, including 4 arrhythmia and 2 myocardial infarction patients. Biventricular volumes were measured, and blood-myocardium contrast and boundary sharpness scores were compared. Results The RT-SVR approach successfully provided 4D cardiac cine for all subjects. Acquisition time was 8:33 ± 1:01 min and 8:27 ± 2:06 min (p = 0.85), blood-myocardium contrast ratio was 2.30 ± 0.58 and 2.38 ± 0.59 (p = 0.33), boundary sharpness was 1.11 ± 0.46 and 1.18 ± 0.53 (p = 0.04), for RT-SVR and breath-hold cine, respectively. Bi-ventricular volumes had good agreement, with an ejection fraction bias of -4.02% (p < 0.05) and -2.30% (p = 0.10) for left and right ventricles, respectively. Conclusion The RT-SVR approach enables 4D cardiac cine with comparable bi-ventricular volumes, contrast, sharpness, and acquisition time compared to standard breath-hold cine while providing additional motion robustness. This approach may be beneficial in patients that are non-cooperative, children, and those with irregular breathing and/or arrhythmia.